A high quality Aotearoa New Zealand dietary pattern adapting a Mediterranean diet for metabolic health: a feasibility study - Amber Parry-Strong; Richard Gearry; Troy L. Merry; Mark Weatherall; Cheryl Davies; Anna Worthington; Rhiane Bishop; Summer Rangimaarie Wright; Fiona E. Lithander; Meika Foster; Jeremy Krebs (BMC Nutrition, 2023)
Abstract Aim To assess the feasibility of a family-based dietary intervention study using a meal kit home delivery service, in people at risk of cardio-metabolic disease. Methods A 12-week dietary intervention feasibility study of adults (termed the index participants) at increased risk of metabolic and cardiovascular disease, enriched for Māori who are indigenous New Zealanders. The study sample also included the household/whānau members living with the index participant. All participants received a 12 week intervention using weekly home delivery of meal kits and groceries consistent with a Mediterranean dietary pattern. Outcomes were the metabolic syndrome severity score (MetSSS); feasibility and acceptability of the intervention; dietary intake; and other clinical and anthropometric measures. Results There were 29 index participants recruited and in addition, 50 household/whānau members took part in the feasibility study. The mean (SD) household/whānau size was 3.45 (1.4) people, and the mean (SD) number of people in each household/whānau who participated in the study was 2.84 (1.2). The feasibility of intervention to households/whānau was proven in this context. The mean (SD) change in MetSSS was 0.03 (0.33), N = 27, P = 0.69 and there was a statistically significant decrease in body weight of 1.37 kg (95% CI 0.11 to 2.62), p = 0.034. The food deliveries were well received, the dinner kits more so than the grocery items. Conclusion It is feasible to recruit individuals and households/whānau to a family-based dietary intervention. Use of a meal kit home delivery service to provide food which is consistent with the intervention dietary pattern was well received. This feasibility study identified improvements to be made such as nutrition behaviour change support, more variety in food provided, more recipes, and better matching of food quantity to family size. Trial registration ANZCTR—ACTRN12621000856819p registered 2.JUN.2021 https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=382021&isReview=true